Dinámica de la agricultura familiar campesina en el cantón Catamayo. - Lizbeth Esperanza, Lapo Paredes (2019)
The present investigation was carried out in the canton of Catamayo located in the province of Loja, with the objective of studying peasant family farming. 120 surveys were applied to focus groups and involved and reviewed relevant information in libraries, public institutions and the internet. 34% of the land is occupied with short cycle crops, 13% with annual crops, 4% mixed garden type, 40% dedicated to natural pastures and 9% corresponds to forests. 60% of families own the land; for the production process they use family and salaried labor, traditional technology and ancestral cultural practices. Three types of rural families were identified: 1) subsistence (60%) oriented to self-consumption, with scarce availability of land and extra-farm activities to complement the basic needs of the family; records a value for income of 5,352 dollars and reaches a value for direct costs of 2,399 dollars; 2) transition (35%) has better access to land, satisfies the requirements of family reproduction and presents difficulties to generate surpluses that allow the reproduction and development of the productive unit; it reaches a value for income of $ 24,681 and a value for direct costs of $ 7,692; and, 3) consolidated (5%), without limiting access to land, with maximization of value added per hectare, hiring labor and generating surpluses for capitalization; this type of family obtains an income value of $ 38,527 and direct costs of $ 15,253. The marketing systems identified are: indirect-long, where the producer is directly linked to an intermediary and this to the retailer; indirect-short, which is articulated to a retailer and transferred to the final consumer; and direct-consumer, your first transaction agent is the final consumer